Relasi Kuasa Pemerintah Dan Guru PAI Dalam Mencegah Paham Radikalisme Di Sekolah Menengah Kejuruan - Tasri Tasri; Hendy Rasyid Kurniawan; Muhammad Nikman Naser (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
The problem in this study is that there are several indicators of radicalism in students in the author's observations at SMK 1 Argamakmur. The government and Islamic Religious Education Teachers try to create a religious atmosphere that can reduce the impact of deviant understanding in schools. The purpose of this study is to find out more about the efforts of the government and Islamic Religious Education Teachers in preventing radicalism at SMK 1 Argamakmur, North Bengkulu Regency. This research is a field research using descriptive qualitative method. Data collection techniques through observation, interviews, and documentation. Data analysis techniques by means of data reduction, data presentation, and conclusions. The results of the study are regulations implemented by the government need to be integrated in the curriculum and Islamic Education learning tools, internalization of anti-radicalism in Islamic Education materials, early socialization, reviving religious activities in the school environment and society. Masalah dalam penelitian ini ada beberapa indikator paham radikalisme pada peserta didik dalam pengamatan penulis di SMK 1 Argamakmur. Pemerintah dan Guru Pendidikan Agama Islam berupaya menciptakan suasana keagamaan yang bisa mengurangi dampak pemahaman yang menyimpang di sekolah. Tujuan penelitian ini ialah untuk mengetahui lebih dalam upaya pemerintah dan Guru Pendidikan Agama Islam dalam mencegah paham radikalisme di SMK 1 Argamakmur Kabupaten Bengkulu Utara. Penelitian ini adalah penelitian lapangan dengan menggunakan metode deskriptif kualitatif. Teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Teknik analisis data dengan cara reduksi data, penyajian data, dan kesimpulan. Hasil dari penelitian adalah regulasi yang diterapkan oleh pemerintah perlu diintegrasikan dalam kurikulum dan perangkat pembelajaran PAI, internalisasi anti radikalisme pada materi Pendidikan Agama Islam, sosialisasi sejak dini, menghidupkan kegiatan keagamaan di lingkungan sekolah dan masyarakat.